EDUCATIONAL FACILITIES NEEDS MANAGEMENT BASED ON POPULATION GROWTH PROJECTIONS JAMBI PROVINCE OF 2023 - Zawaqi Afdal Jamil; Imam Arifaillah Huda; Bayu Kurniawan (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
This study aims to develop a pattern of planning for educational facilities in the education management system in Jambi Province based on the projection of population growth in Jambi Province in 2023. The method used in this study is the quantitative method. The data collection method was carried out by literature study, and secondary data study from the Central Statistics Agency of Jambi Province. The results showed that the projected population growth in 2023 experienced different trends in each district and city. Population growth projections provide a real picture of school needs for junior high school & senior high school. This trend indicates a strong direction of management functionalization in planning aspects for local governments to meet the needs of educational facilities junior high school & senior high school which are relatively balanced with the population. Analysis of the results of the calculation of the number of school availability with the population in each region is relatively less balanced. This happens because one of the main factors, namely planning for school needs, is not based on information and projected data for calculating population growth in the area. The results showed that the areas that did not need to add junior high schools until 2023 were Kerinci, Merangin, Sarolangun, Batanghari, Muaro Jambi, East Tanjung Jabung, West Tanjung Jabung, Tebo, Bungo districts. On the other hand, the areas that require an additional number of junior high schools are the City of Jambi as many as 32 and the City of Sungai Penuh with 3 schools. For the senior high school, all districts in Jambi Province require additional schools. Therefore, it is suggested to the Government and Regional Governments to develop plans based on population growth projections so that there is an even distribution of educational facilities so that inequality between regions can be minimized..Key words: population growth projections, educational facilities, management, planning